Natural Selection Shapes Maintenance of Orthologous sRNAs in Divergent Host-Restricted Bacterial Genomes. (2nd July 2021) - Thairu, Margaret W; Meduri, Venkata Rama Sravani; Degnan, Patrick H; Hansen, Allison K
Abstract: Historically it has been difficult to study the evolution of bacterial small RNAs (sRNAs) across distantly related species. For example, identifying homologs of sRNAs is often difficult in genomes that have undergone multiple structural rearrangements. Also, some types of regulatory sRNAs evolve at rapid rates. The high degree of genomic synteny among divergent host-restricted bacterial lineages, including intracellular symbionts, is conducive to sRNA maintenance and homolog identification. In turn, symbiont genomes can provide us with novel insights into sRNA evolution. Here, we examine the sRNA expression profile of the obligate symbiont of psyllids, Carsonella ruddii, which has one of the smallest cellular genomes described. Using RNA-seq, we identified 36 and 32 antisense sRNAs (asRNAs) expressed by Carsonella from the psyllids Bactericera cockerelli ( Carsonella-BC ) and Diaphorina citri ( Carsonella-DC ), respectively . The majority of these asRNAs were associated with genes that are involved in essential amino acid biosynthetic pathways . Eleven of the asRNAs were conserved in both Carsonella lineages and the majority were maintained by selection. Notably, five of the corresponding coding sequences are also the targets of conserved asRNAs in a distantly related insect symbiont, Buchnera. We detected differential expression of two asRNAs for genes involved in arginine and leucine biosynthesis occurring between two distinct Carsonella-BC life stages. Using asRNAs identified in Carsonella, Buchnera, and Profftella which are all endosymbionts, and Escherichia coli, we determined that regions upstream of these asRNAs encode unique conserved patterns of AT/GC richness, GC skew, and sequence motifs which may be involved in asRNA regulation.